Mock light-cones and theory friendly catalogues for the CANDELS survey. Issue 4 (29th January 2021) - Somerville, Rachel S; Olsen, Charlotte; Yung, L Y Aaron; Pacifici, Camilla; Ferguson, Henry C; Behroozi, Peter; Osborne, Shannon; Wechsler, Risa H; Pandya, Viraj; Faber, Sandra M; Primack, Joel R; Dekel, Avishai
ABSTRACT: We present mock catalogues created to support the interpretation of the Cosmic Assembly Near-IR Deep Extragalactic Legacy Survey (CANDELS). We extract haloes along past light-cones from the Bolshoi Planck dissipationless N-body simulations and populate these haloes with galaxies using two different independently developed semi-analytic models of galaxy formation and the empirical model universemachine . Our mock catalogues have geometries that encompass the footprints of observations associated with the five CANDELS fields. In order to allow field-to-field variance to be explored, we have created eight realizations of each field. In this paper, we present comparisons with observable global galaxy properties, including counts in observed frame bands, luminosity functions, colour–magnitude distributions and colour–colour distributions. We additionally present comparisons with physical galaxy parameters derived from SED fitting for the CANDELS observations, such as stellar masses and star formation rates. We find relatively good agreement between the model predictions and CANDELS observations for luminosity and stellar mass functions. We find poorer agreement for colours and star formation rate distributions. All of the mock light-cones as well as curated 'theory friendly' versions of the observational CANDELS catalogues are made available through a web-based data hub.